Discrepancy in p16 expression in patients with HPV-associated head and neck squamous cell carcinoma in Thailand: clinical characteristics and survival outcomes - Lalida Arsa (2022)
Background: Lower prevalence HPV infection has been previously reported in Thai population when compared with Western countries. p16 expression indicates HPV-associated oropharyngeal squamous cell carcinoma (OPSCC), but not non-OPSCC. We therefore evaluated the characteristic and association of p16 and HPV in Thai patients with HNSCC. Methods: We used immunohistochemistry and qPCR, respectively, to detect p16 and HPV DNA in archrival formalin-fixed paraffin-embedded HNSCC tissues. Patient characteristics and survival were analyzed. Results: p16 expression was detected in tumors of 72 of 662 (10.9%) patients with HNSCC and was significantly associated with higher-grade histology, advanced nodal stage, and oropharynx. p16 was expressed in 28 and 6.5% of patients with OPSCC or non-OPSCC, respectively, and HPV DNA was detected in 15.6 and 1% of patients, respectively. Using p16 as a surrogate for HPV status, sensitivities were 80 and 25% in OPSCC and non-OPSCC, respectively. Positive and negative predictive rates of OPSCC were 38 and 95%. Discordance rates between HPV and p16 were 23 and 7% in OPSCC and non-OPSCC, respectively. Overall survival (OS) were significantly longer in both p16-positive OPSCC (p = 0.049), and non-OPSCC (p = 0.003). Conclusions: Low prevalence of p16 and HPV associated OPSCC and non-OPSCC were confirmed in Thai patients. High discordance and low positive predictive rates of p16 were observed in HPV-associated OPSCC. p16 was a significant prognostic factor for OS for patients with OPSCC or non-OPSCC. Therefore, HPV testing should be performed to assess the association of HPV with HNSCC regardless of p16 expression.